Critical notes on the concept of hegemony in Dussel and Laclau (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
This article studies the fundamental aspects of Dussel’s critique of the formal model of hegemony developed by Laclau. In this context, a concept of popular hegemony tied to the centrality of the reproduction of life as a normative criterion in politics is proposed, as well as an argument against the abstract decisionism of the populist theory of Laclau.  The text also offers –as suggested by Castro-Gomez’s reading– a critique of Dussel’s ideas from a post-foundationalist perspective, which leads to questioning the very idea of an unconditional universal.  Finally, we conclude by positing a critique of some of the theoretical viewpoints shared by both authors, identifying the limitations of the very concept of hegemony.
Keywords: Hegemony; populism; politics; neoliberalism